Optimal sequential investigation rules in competition law - Wolfgang Kerber; Jürgen-Peter Kretschmer; Georg von Wangenheim (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
Although both in US antitrust and European competition law there is a clear evolution to a much broader application of rule of reason (instead of per-se rules), there is also an increasing awareness of the problems of a case-by-case approach. The error costs approach (minimizing the sum of welfare costs of decision errors and administrative costs) allows not only to decide between these two extremes, but also to design optimally differentiated rules (with an optimal depth of investigation) as intermediate solutions between simple per-se rules and a fullscale rule of reason. In this paper we present a decision-theoretic model that can be used as an instrument for deriving optimal rules for a sequential investigation process in competition law. Such a sequential investigation can be interpreted as a step-by-step sorting process into ever smaller subclasses of cases that help to discriminate better between pro- and anticompetitive cases. We analyze both the problem of optimal stopping of the investigation and optimal sequencing of the assessment criteria in an investigation. To illustrate, we show how a more differentiated rule on resale price maintenance could be derived after the rejection of its per-se prohibition by the US Supreme Court in the Leegin case 2007.
Keywords: K20; K21; K40; D81; 330; Law Enforcement; Decision-Making; Competition Law; Antitrust Law